MEMBANGUN KESADARAN HUKUM MASYARAKAT MELALUI LAYANAN BANTUAN HUKUM BAGI MASYARAKAT MISKIN DI DESA BATUR KABUPATEN PROBOLINGGO - Susantyo, Herdy Pratama; Syahbana, Ahmad Nabiel; Haji, Moh Samsul; Azzuhdi, Imam Mujtahid; Afandi, Ahmad (Abdi Panca Marga, 2024)
Legal aid services are a forum for a person or group of poor people to gain understanding and legal protection if a problem occurs in their area. Legal Aid Services (LBH) there is a new hope for the community to help them to try to find justice in various fields of law, especially for those who are categorized as financially and socially disadvantaged and do not understand well the legal rules that apply in Indonesia today, it is hoped that with this community service can develop knowledge of the functions and benefits of legal aid facilitated by the State. With the existence of legal aid for the poor as an alternative to achieve justice, benefits and legal certainty. Judicial institutions through legal aid services are obliged to provide free legal aid to legal seekers and are prohibited from refusing what is an obligation as intended in the sense of providing free legal aid as a form of service to the poor or needy. However, the people of Batur Village, Probolinggo Regency, currently some still do not know that this free legal aid is available to those who are financially disadvantaged. Especially for those who live in areas far from cities or remote villages, legal knowledge is minimal (layman) in terms of the development of information related to the existence of legal aid services. In connection with this, the purpose of carrying out this community service is to empower the community, educate and find solutions to increase awareness of the rule of law, especially the case that is currently happening in Batur Village regarding Domestic violence (Domestic Violence) that always occurs in the village. Based on the settlement of the above cases, the method used in this activity is socialization/education of legal aid for the poor to increase legal awareness in Batur Village, Probolinggo Regency. Keywords: legal awareness, legal aid services, poor community.